Changes in Functional Outcome Over the First Year After Stroke: An Observational Study From the Swedish Stroke Register. Issue 2 (February 2015) - Ullberg, Teresa; Zia, Elisabet; Petersson, Jesper; Norrving, Bo
Abstract : Background and Purpose—: Large longitudinal studies on stroke outcome are scarce. The aim of this study was to analyze predictors and changes in functional outcome during the first year poststroke. Methods—: Data on patients who were independent in activities of daily living (ADL) and hospitalized for acute stroke in 2008 to 2010 were obtained from the Swedish Stroke Register. Case fatality was assessed by linkage to the Swedish Population Register. ADL was defined by independence or dependence in dressing, toileting, and indoor mobility and assessed at 3 and 12 months. Predictors of ADL dependency were assessed through multivariate analysis. Results—: In total, 64 746 patients were included. Case fatality at 3 months was 13.1% (men 11.6% versus women 14.8%; P <0.0001) and at 12 months 18.2% (men 16.4% versus women 20.3%; P <0, 0001). In the 35 064 followed-up survivors, ADL dependency rates at 3 and 12 months were 16.2% (men 15.9% versus women 19.2%; P <0.0001) and 28.3% (men 22.7% versus women 34.9%, P <0.0001), respectively. Factors predicting deterioration to ADL dependency between 3 and 12 months were female sex (relative risk [RR]=1.56; 95% confidence interval [CI], 1.50–1.70), diabetes mellitus (RR=1.50; 95% CI, 1.05–1.60), comatose at admittance (RR=2.34; 95% CI, 1.79–3.05), previous stroke (RR=1.52; 95% CI, 1.43–1.61), hemorrhagic or unspecified stroke (RR=1.14; 95% CI, 1.05–1.25), and atrial fibrillation (RR= 1.11; 95% CI, 1.04–1.17). Conclusions—: Transition from ADL independence to dependence was observed in a high proportion of patients between 3 and 12 months, challenging the common belief that functioning after stroke is stable beyond 3 months. Deterioration occurred more commonly in women, among whom 1/6 converted to dependency. Abstract : Supplemental Digital Content is available in the text.